New criminal law responses of the Republic of Serbia to violence against women - Jovanović Slađana (Temida)
The Republic of Serbia, within the framework of (intolerably) frequent amendments to the criminal legislation (often rooted in populist demands), has also improved its response to violence against women, which is the subject of this paper. In the first place, new criminal offences have been analyzed, as well as the more severe legislative penal policy, the main features of the Law on the Prevention of Domestic Violence, and the link between the legal framework and the judicial practice, in order to point out the existing shortcomings. The author concludes that changes in approaches are most often explained as necessity due to European integration, and harmonization with the EU law (in the field of protection of women from violence, for which the Council of Europe Convention on Preventing and Combating Violence against Women and Domestic Violence is of particular importance), so there is an impression that the changes are more formal, declarative and not well-thought-out.